F. ARÉVALO Y LAS CORRECCIONES AL TEXTO DE PRUDENCIO - Gallego Moya, Elena (Myrtia, 1998)
The criticism that Arévalo made to the editor that had tried to correct some mistakes in Prudence’s work is analised and valued. He considered that these "correction" came from the ignorance of the characteristics of the latin of that age and they spoilt the text. Bergman or Cunningham agree with Arévalo in their modern editions. The passages studied are: Pe. 3, 64; Pe. 3, 209; C7, 7; C7, 24; C7, 98; C7, 134; C7, 161.